The Relationship Between Materialistic Worldviews and the Level of Belief in Revelation Among Grade V–VI Students at SDN 5 Teluk Nangka - Cesa; Fakhruddin Ahmad Darwis; Benny Prasetiya (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
The This study aims to determine the relationship between materialistic views and the level of belief in revelation in grades V–VI of SDN 5 Teluk Nangka. This topic was chosen because the development of elementary school-aged children's mindsets is starting to be influenced by the social environment, media, and technological advances that have the potential to shape a materialistic orientation and influence their understanding of religious teachings, especially the concept of revelation as a source of divine truth. The study used a quantitative approach with a correlational design. The research sample was fifth and sixth grade students determined through a total sampling technique. Data were collected using a closed questionnaire that had been tested for validity and reliability, then analyzed using the Pearson correlation test to determine the strength and direction of the relationship between variables. The results of the study showed a significant negative relationship between materialistic views and the level of belief in revelation, where students who have a higher materialistic tendency tend to show a lower level of belief in revelation. This finding suggests that a value orientation that emphasizes material aspects can influence the formation of religious attitudes in elementary school-aged children. Therefore, the results of this study are important as a basis for schools and parents in strengthening character education and spiritual values to balance the intellectual and moral development of students.